MicroRNA expression profiling for the prediction of resistance to neoadjuvant radiochemotherapy in squamous cell carcinoma of the esophagus - Slotta-Huspenina, Julia; Drecoll, Enken; Feith, Marcus; Habermehl, Daniel; Combs, Stephanie; Weichert, Wilko; Bettstetter, Marcus; Becker, Karen; Langer, Rupert (Journal of Translational Medicine, 2018)
Background: MicroRNAs (miRNAs) play an important role in cancer biology. Neoadjuvant radiochemotherapy followed by surgery is a standard treatment for locally advanced esophageal squamous cell carcinoma (ESCC). However, a subset of patients do not respond. We evaluated whether miRNA profiles can predict resistance to radiochemotherapy. Methods: Formalin-fixed, paraffin-embedded pretherapeutic biopsies of patients treated by radiochemotherapy followed by esophagectomy were analyzed. The response was determined by histopathological tumor regression grading. miRNA profiling was performed by microarray analysis (Agilent platform) in 16 non-responders and 15 responders. Differentially expressed miRNAs were confirmed by real-time quantitative PCR (qRT-PCR) in an expanded cohort of 53 cases. Results: The miRNA profiles within and between non-responders and responders were highly similar (r = 0.96, 0.94 and 0.95). However, 12 miRNAs were differentially expressed (> twofold; p ≤ 0.025): non-responders showed upregulation of hsa-miR-1323, hsa-miR-3678-3p, hsv2-miR-H7-3p, hsa-miR-194∗, hsa-miR-3152, kshv-miR-K12-4-3p, hsamiR- 665 and hsa-miR-3659 and downregulation of hsa-miR-126∗, hsa-miR-484, hsa-miR-330-3p and hsa-miR-3653. qRT-PCR analysis confirmed the microarray findings for hsa-miR-194∗and hsa-miR-665 (p < 0.001 each) with AUC values of 0.811 (95% CI 0.694-0.927) and 0.817 (95% CI 0.704-0.930), respectively, in ROC analysis. Conclusions: Our results indicate that miRNAs are involved in the therapeutic response in ESCC and suggest that miRNA profiles could facilitate pretherapeutic patient selection.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Esophagus; miRNA; Neoadjuvant therapy; Response; Squamous cell carcinoma